Ethnography: The Initial Steps of Leadership Ipuk-Sugirah Leading Banyuwangi - Subaharianto, Andang (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The Banyuwangi Regency General Election Commission through the Banyuwangi Regency KPU Decree No. 15/HK.03.1-Kpt/3510/KPU-Kab/II/2021 dated February 18, 2021, determined the Ipuk-Sugirah pair as Regent and Deputy Regent who won in the Pilkada contestation Banyuwangi 2020. An interesting thing was conveyed by the regent in focusing on economic recovery due to the COVID-19 pandemic. Of course, we hope that the goal of economic recovery will run smoothly and the indicators will be achieved. In the economic recovery section due to the COVID-19 pandemic, there are 7 points that are the targets of renewal. The problem that occurs in people's lives is that an increase in per capita income may not raise people's real living standards. The infrastructure development policy that prioritizes villages as passive patronage is a policy that is close to the welfare barn. Considering the potential of the village is the closest potential to ensure welfare, these glasses are certainly very difficult to find when the orientation of the leader is only limited to developmentalism but when the orientation of the leader is focused on the interests of the community, of course, the theory of social analysis needs to be developed. This Writing Method Is Descriptive. Descriptive method is a method that aims to describe or provide an overview of the object under study through data or samples that have been collected as they are without analyzing and making conclusions that apply to the public. The Covid-19 pandemic has proven not only to destroy the economy. But, also killing humans en masse. It's not just about killing large numbers of people. But it also kills the hopes of many people. Society is overshadowed by anxiety, confusion, and helplessness. His life is threatened, his source of livelihood is also threatened. Not in a short time. In Indonesia since the beginning of 2020. No one can confirm the stopping point. All of this can lead to despair. The situation for Ipuk – Sugirah's departure was very different. Let's look at the initial energy. Ipuk – Sugirah started the government with a significantly lower APBD. The 2020 APBD is 3.3 trillion rupiah. Ipuk - Sugirah started her government with the 2021 APBD of 2.7 trillion. Down about 600 billion rupiah. Certainly not a small number for the size of the district.